Evaluation of Oxidative Stress and the Efficacy of Antioxidant Treatment in Diabetes Mellitus - Enikő, Nemes-Nagy; Balogh-Sămărghiţan, V.; Crăciun, Elena Cristina; Morar, R.; Pusta, Dana Liana; Zita, Fazakas; Terézia, Szőcs-Molnár; Iulia, Dunca; Dóra, Sánta; Dobreanu, Minodora (IntechOpen, 2012)
None